The Impact of Uncertainty on Customer Satisfaction - Camila Back; Martin Spann (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2022)
Customer satisfaction is an important metric to predict customer behavior and as a result firms' profitability. Expectations of a product's performance serve as a reference point against which customers evaluate their satisfaction with the products' actual performance. However, what is the effect of uncertainty in expectations? This paper develops a novel theoretical model of satisfaction, in which expectations reflect distributions of individual beliefs about performance outcomes. Based on this model, uncertainty shifts subjective reference points upward. That is, uncertainty increases the performance level at which customers switch from being dissatisfied to being satisfied. Furthermore, uncertainty has an attenuating effect on both positive and negative deviations of actual performance from subjective reference points. Put differently, a bad performance feels less bad and a good performance feels less good when it is expected, compared with unexpected. The authors find support for the model's predictions in an experimental study on product delivery as well as a field study based on online reviews. In addition, the authors develop a model-based tool that predicts the effect of uncertainty on customer satisfaction across different customizable scenarios. The paper's results carry implications for firms' communication, customer valuation and recovery strategies.
Keywords: 330; customer satisfaction; uncertainty; probabilistic beliefs; prospect theory